Nonaqueous synthesis and characterization of capped alpha-Fe2O3 nanoparticles from iron(III) hydroxy-oleate precursor - Chikate, Rajeev C.; Jun, Ki-Won; Rode, Chandrasekhar V. (Polyhedron, 2008)
The synthesis of capped alpha-Fe2O3 nanoparticles from thermal treatment of iron (III) hydroxy-oleate in boiling organic solvents around 250 degrees C with retention of the integrity of the oleate units during the reaction process is reported. The formation of capped iron oxide particles is accomplished under aerobic conditions while the solvents used in the synthesis have strong influence on the nature and morphology of nanoparticles. These nanoparticles are studied by means of X-ray powder diffraction, IR and XPS while the morphology and particle size of nanocrystals are evaluated using SEM and TEM analysis suggesting the formation of monocrystalline alpha-Fe2O3 particles having cubical and spherical morphologies with sizes ranging from 20 to 30 nm. This organophilic material with oleate capping around the surfaces can be readily dispersed in organic solvents thus forming organosols. These organosols exhibit band-edge emission photoluminescence band both in toluene as well as in solid state while FT-IR analysis reveals formation oleate capped nanoparticles The XPS data indicate ferric state having doublet from Fe 2P(3/2) and Fe 2p(1/2) core-level electrons. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: alpha-Fe2O3; capped nanoparticles; cubic morphology; ferrofluids; nonaqueous synthesis; Oleic acid; organosol

Selective catalytic oxidation of geraniol to citral with molecular oxygen in supercritical carbon dioxide - Dapurkar, Sudhir E.; Kawanami, Hajime; Chatterjee, Maya; Rode, Chandrasekhar V.; Yokoyama, Toshirou; Ikushima, Yutaka (Applied Catalysis A-General, 2011)
Selective catalytic oxidation of geraniol to citral with molecular oxygen in supercritical carbon dioxide (scCO(2)) has been investigated. The catalyst used was a chromium containing mesoporous molecular sieve catalyst viz. CrMCM-41. Comparison studies were performed with CoMCM-41. PtMCM-41 and PdMCM-41 catalysts. Among the various catalysts studied. CrMCM-41 showed a high conversion of geraniol and an excellent selectivity for citral. In contrast CoMCM-41, PtMCM-41 and PdMCM-41 catalysts exhibited low conversion of geraniol. However all three catalysts compared showed similar citral selectivity to CrMCM-41. The effect of CO(2) pressure and reaction temperature geraniol oxidation was studied with CrMCM-41. Supercritical CO(2) medium was found to enhance the conversion of geraniol and/or yield of citral. It was noticed that the catalyst can be recycled with negligible loss of conversion. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Citral; Geraniol; heterogeneous catalyst; Molecular oxygen; Selective oxidation; Supercritical carbon dioxide

Robust highly flexible all-solid-state micro pseudocapacitor based on ternary oxide CuCo2O4 having ultrathin porous nanowall type morphology blended with CNT - Basu, Aniruddha; Bhardwaj, Monika; Gawli, Yogesh; Rode, Chandrasekhar V.; Ogale, Satishchandra B. (Chemistryselect, 2016)
In this work we demonstrate a facile approach to the fabrication of all solid state flexible interdigitated micro pseudocapacitor device using pre-synthesized CuCo2O4 (CCO) ternary metal oxide as the electrode material. The hydrothermally synthesized CCO exhibits a peculiar 3D interconnected aligned porous nanowall type morphology which is highly desirable for storage as well as charge transfer. The device is fabricated using CO2 laser scribing technique and the PVA-H3PO4 gel electrolyte is used as the electrolyte. The as-synthesized CCO as well as its blend with 10 wt.% CNT are examined for the electrochemical performance. CNT blending is shown to reduce the charge transfer resistance dramatically, thereby enhancing the pseudo capacitance. The areal capacitance of 2.29 mF cm(-2) is obtained from the solid state device. Moreover, the CCO-CNT electrode also shows a high stability upto 9000 cycles without a sign of further decay. Importantly, the devices also retain over 65% of their initial capacitance after 1000 large angle (608) bending cycles and 93% of the initial capacitance under 1208 bending condition, thanks to the mechanical flexibility afforded by CNTs without disrupting conducting paths.